ANALISIS YURIDIS SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 TENTANG PETUNJUK BAGI HAKIM DALAM MENGADILI PERKARA PERMOHONAN PENCATATAN PERKAWINAN ANTAR-UMAT YANG BERBEDA AGAMA DAN KEPERCAYAAN TERHADAP PASAL 35 HURUF a UNDANG-UNDANG NOMOR 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN - Simatupang, Gavrila Eleazar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Supreme Court issued Supreme Court Circular Letter Number 2 of 2023 whichexplains the prohibition on judges throughout Indonesia from granting requests forregistration of interfaith marriages. Where this rule is in conflict with Article 35 Letter a ofLaw Number 23 of 2006. The issuance of SEMA resulted in a setback that hampered thedevelopment of the justice system in guaranteeing the rights of citizens from variousbackgrounds. It can be concluded that SEMA Number 2 of 2023 issued by the chairman ofthe Supreme Court has violated its constitutionality.The type of research used by the author is normative legal research or what is knownas